The role of governance in choosing appropriate accounting policies for companies listed on the Sudanese Khartoum Stock Exchange (Entrepreneurship Journal for Finance and Business, 2026)
The research aimed to identify the role of governance in selecting appropriate accounting policies for companies listed on the Khartoum Stock Exchange in Sudan. This was achieved by exploring the possibility of finding a statistically significant relationship between audit committees and the selection of alternative accounting policies for companies listed on the Khartoum Stock Exchange, the possibility of finding a statistically significant relationship between internal audit information and the selection of accounting policies for economic companies listed on the Khartoum Stock Exchange, and the possibility of finding a statistically significant relationship between external auditor reports and the selection of alternative accounting policies for companies listed on the Khartoum Stock Exchange. The research followed a descriptive-analytical approach, and a sample was distributed to the study population, which consisted of companies listed on the Khartoum Stock Exchange. The sample was selected from individuals in a manner appropriate to their job titles. The researcher distributed (55) questionnaires to the target group, and (50) individuals responded, meaning that the questionnaire was returned at a rate of (90%). The data collected from the questionnaire was then analyzed. After the study and analysis, the research concluded that there is a statistically significant relationship between audit committees and the selection of alternative accounting policies for companies listed on the Khartoum Stock Exchange, through the presence of a committee to review accounting policies and principles. The study, conducted in companies with the board of directors, focuses on selecting appropriate accounting policies for financial reporting and discussing with management how to choose accounting estimates. It also examines the statistically significant relationship between internal audit information and the selection of alternative accounting policies for companies listed on the Khartoum Stock Exchange. This is achieved through the contribution of internal audit information to governance, enhancing credibility and fairness for companies, and reducing the risks of administrative and financial corruption. The research recommends that companies and institutions increase their focus on the concept of governance and work to adopt and develop it to contribute to improving the financial and administrative performance of emerging, developing, and established companies.